Navigating Human Immunodeficiency Virus and Primary Care Concerns Specific to the Transgender and Gender-Nonbinary Population. (23rd March 2022) - Lieber, Mark; Hamill, Matthew M; Pham, Paul; Pine, Elyse; Crank, Jill; Shah, Maunank
Abstract: Human immunodeficiency virus (HIV) prevention and treatment remain critically important to outpatient care among transgender and gender-nonbinary individuals. Epidemiologically, trans men and trans women are significantly more likely to have HIV compared with all adults of reproductive age. Here, we provide an overview of unique primary care considerations affecting transgender and gender-nonbinary individuals, including screening and treatment of HIV and other sexually transmitted infections as well as cancer screening and fertility preservation options. We also seek to review current literature and clinical practice guidelines related to drug–drug interactions between antiretroviral therapy (ART) and gender-affirming hormonal therapy (GAHT). In short, integrase strand transfer inhibitor–based therapy is not expected to have significant drug interactions with most GAHT and is preferred in most transgender individuals, including those on GAHT. Clinicians should also remain aware of current GAHT regimens and consider tailoring ART and GAHT to reduce cardiovascular and other risk factors.